CONSUMER PERCEPTION OF STORE BRAND AND NATIONAL BRAND IN HYPERMART MANADO - Bawata, Nancy; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Coffee is one global community of beverage that is consumed by many people in this world. The Consumer Perception on Brand, especially for coffee commodity, is changed based on the understanding of Promotion Perception, Product Perception, Price Perception, Store Perception, Self-perception and Perception Risk. In this research, the main objective is to figure out whether there is any significant difference for Consumer Perception on Brand concept between Luwak White Coffee consumers and Value Plus Coffee consumers in Manado. For accomplishing this essential purpose, the Independent Sample t-test is employed to tabulate the obtained analyzed data. The results in this current research, it is found out that Luwak White Coffee consumers has the more dominant influence for the perception of Product Perception, Price Perception and Self-perception for packaged coffee products and Value Plus Coffee consumers has the more dominant influence for the perception of Promotion Perception, Store Perception and Perception Risk and the Consumer Perception on Brand for packaged coffee products; and there is no significant difference for Promotion Perception factor, Product Perception factor, Price Perception factor, Store Perception factor, Self-perception factor, Perception Risk factor and the Consumer Perception on Brand factor between Luwak White Coffee consumers and Value Plus Coffee consumers in Manado. Keywords: consumer perception, brand, white coffee